Assessment of Students’ Attitude towards Learning Communication Skills: An Exploratory Study - Tripathi, Rupam; Tripathi, Navin; Tripathi, Malati; Shrestha, Rubina; Kesari, Dheeraj; Chhetri, Pradip (Journal of Universal College of Medical Sciences, 2019)
INTRODUCTION: Good communication skills can increase the health-care providers' diagnostic efficiency and decision making ability, as well as lead to improved patient satisfaction. The aim of this study is to determine the attitude associated with learning communication skills among dental and medical students. MATERIAL AND METHODS: A descriptive study was conducted among 231 students, studying in Universal College Of Medical Sciences (UCMS), College of Dental Surgery, Bhairahawa, Nepal using a standardized pro forma which consisted of questions on general information and of communication skills using validated Communication Skills Attitude Scale. For statistical analysis, Mann-Whitney U test and Kruskal-Wallis test were applied. RESULTS: Students indicate high levels of positive attitudes and low levels of negative attitudes. Attitudinal scores differ insignificantly in relation to gender. CONCLUSION: Medical and dental students in our study show basically a positive approach. Further investigation is necessary to explore and understand attitudes towards communication skills of medical and dental undergraduates.